Characterisation of electrochemical transducers for biosensor applications - Wan Salim, Wan Wardatul Amani; Shohibuddin, Ihda Uswatun Shalihah (2019)
Biosensors are devices that detect and report the presence or quantity of a particular analyte. Among the biosensor components, a physicochemical transducer measures physical and chemical changes from analyte recognition interactions where products, by-products, intermediates, or physical changes are converted into a measurable signal. The character of the transducer determines the performance of a biosensor; hence the characterisation of the transduction is crucial in the design of a biosensor. This workshop will demonstrate electrochemical characterisation of the transducer layer of a biosensor via cyclic voltammetry